COMPARISON OF THE EFFECTIVENESS OF GIVING GINGER AND HONEY WITH GINGER, GREEN BEANS AND HONEY TO OVERCOME NAUSEA AND VOMITING IN FIRST TRIMESTER PREGNANT WOMEN - Mulyani, Yanyan; Rofiasari, Linda (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2022)
Nausea and vomiting are common discomforts experienced by 50% of pregnant women. The purpose of this study was to compare the effectiveness of giving ginger and honey with ginger, green beans and honey to treat nausea and vomiting in first trimester pregnant women. The quantitative research design used a quasi-experimental. Subjects in this study were taken by Consecutive sampling as many as 60 respondents. The results showed that most (63.3%) pregnant women in the first trimester experienced mild nausea and vomiting after being given the intervention of ginger, honey, and green beans. While in the honey and ginger intervention group, most (46.7%) experienced moderate nausea and vomiting. The results of the statistical test showed p-value = 0.007 (0.05), meaning that there was a difference in effectiveness between the ginger and honey intervention, with the ginger, honey, and mung bean intervention. The mean rank value in the Mann-Whitney test shows the average rating for giving ginger, honey and green beans, which is 24.90, lower than the average rating for giving honey and ginger with a value of 36.10. This means that ginger, honey, and green beans are more effective in overcoming nausea and vomiting in first trimester pregnant women compared to giving ginger and honey. The conclusion is that giving ginger, green beans, honey is effective compared to giving ginger, honey so that it can be an alternative in overcoming nausea and vomiting for pregnant women in the first trimester.